ADVANCE CARE PLANNING AMONG ETHNIC/RACIAL MINORITY OLDER ADULTS USING NATIONAL HEALTH AGING AND TRENDS SURVEY. (11th November 2018) - Hong, M; Kim, K
Abstract: Given the increasing number ethnic minority older adults in the U.S., there is a growing attention toward their engagement in advance care planning (ACP) because of its positive effects on the quality of end-life care. The purpose of the study was to describe and identify factors affecting engagement in three different types of ACP such as informal talk, living will (LW), and durable power of attorney for health care (DPAH) among ethnic minority older adults. Data was drawn from the second wave of the National Health Aging and Trends Survey. A total of 543 older adults who identified themselves as an ethnic/racial minority and completed the questions about ACP were included in our study. The descriptive results showed the highest level of engagement in informal talk (60%) compared to LW (26.5%) and DPAH (30%). Informal talks happened mostly with adult children (57.7%) and they were frequently designated as surrogate decision makers (70.7%). Multivariate logistic regression analyses revealed that a higher level of education and greater preference toward life-sustaining treatment were associated with all three types of ACP engagement. Ethnicity (Non-Hispanic others compared to blacks), multimorbidity, and being born in the U.S. were associated with informal talk. Marital status (Married compared to never married) was related to LW completion whereas interview language (English) was associated with DPAH completion. These findings indicate that informal talk, LW, and DPAH may have different facilitators and barriers, suggesting the necessity of developing targeted strategies to promote each type of ACP for ethnic minority older adults.